Silane grafted natural rubber and its compatibilization effect on silica-reinforced rubber tire compounds - K. Sengloyluan; K. Sahakaro; W. K. Dierkes; J. W. M. Noordermeer (eXPRESS Polymer Letters)
Natural Rubber (NR) grafted with 3-octanoylthio-1-propyltriethoxysilane (NXT) was prepared by melt mixing using 1,1′-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane as initiator at 140 °C with NXT contents of 10 and 20 parts per hundred rubber [phr] and initiator 0.1 phr. The silane grafted on NR molecules was confirmed by Fourier transform infrared (FTIR), proton nuclear magnetic resonance (1H-NMR) and scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM-EDX). Based on 1H-NMR, the use of 10 and 20 phr (parts per hundred resin) of silane resulted in grafted NXT onto NR of 0.66 and 1.32 mol%, respectively, or a grafting efficiency of approx. 38%. The use of NXT-grafted NR as compatibilizer in silica-filled NR compounds, to give a total amount of NXT in both grafted and non-grafted forms in the range of 0.8–6.1 wt% relative to the silica, decreases the Mooney viscosity and Payne effect of the compounds, improves filler-rubber interaction, and significantly increases the tensile properties of the silica-filled NR-compounds compared to the non-compatibilized one. At the same silane-content, the use of silane-grafted NR gives slightly better properties than the straight use of the same silane. With sulfur compensation, the use of NXT-grafted-NR with about 6 wt% NXT relative to the silica gives technical properties that reach the levels obtained for straight use of bis-(3-triethoxysilyl-propyl)tetrasulfide (TESPT) at 8.6 wt% relative to the silica.